1968
DOI: 10.4095/300148
|View full text |Cite
|
Sign up to set email alerts
|

The grain-size dependence of the electromechanical properties in lead zirconate titanate ceramics

Abstract: The dependence of the electromechanical properties of unmodified lead zirconate-titanate ceramics on the grain size of the ceramic has been determined for materials with compositions on both sides of the rhombohedral/ tetragonal boundary. High-density ceramics with average grain diameters from about 1.5 ?m to 8 ?m were examined. It was found that the dielectric constant before poling, and the dielectric and mechanical losses all decreased with increasing grain size. The coercive field was found to be largely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…[22][23][24][25][26] It was shown that the remanent polarisation, the piezoelectric coefficients and the coupling factors decrease with decreasing grain size of the ceramic. [22][23][24][25][26] If additional phases at the grain boundaries can be excluded, the reasons for the drop of the properties are space charges 25 and mechanical stress. 23,24 The mechanical stress has an effect on the crystal lattice which was proved by Randall et al 25 In this study, the correlation between the morphotropic phase boundary and the grain size of neodymium doped PZT ceramics is investigated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[22][23][24][25][26] It was shown that the remanent polarisation, the piezoelectric coefficients and the coupling factors decrease with decreasing grain size of the ceramic. [22][23][24][25][26] If additional phases at the grain boundaries can be excluded, the reasons for the drop of the properties are space charges 25 and mechanical stress. 23,24 The mechanical stress has an effect on the crystal lattice which was proved by Randall et al 25 In this study, the correlation between the morphotropic phase boundary and the grain size of neodymium doped PZT ceramics is investigated.…”
Section: Introductionmentioning
confidence: 98%
“…[22][23][24][25][26] If additional phases at the grain boundaries can be excluded, the reasons for the drop of the properties are space charges 25 and mechanical stress. 23,24 The mechanical stress has an effect on the crystal lattice which was proved by Randall et al 25 In this study, the correlation between the morphotropic phase boundary and the grain size of neodymium doped PZT ceramics is investigated. The ceramic material was fabricated after a sol-gel method developed for the synthesis of fine scaled PZT fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Donor and acceptor doping are used to obtain so-called ''soft'' and ''hard'' PZT materials, respectively. [3][4][5][6][7][8][9][10][11][12][13] Properties contrasting the elastodielectric properties in hard and soft PZT are given in Table I. There have been many earlier attempts to investigate the influence of grain size on the piezoelectric properties in PZT ceramics. In general, grain-size studies were limited in a range of 1.0-10 m in bulk ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…By using different of types additive the properties of the PZT system can be changed. Donor and acceptor doping are used to obtain so-called ''soft" and ''hard'' PZT materials, respectively [10][11][12][13][14][15][16].There are several substitution of elements (La, Nd, etc.) on Pb side gives rise to hard and soft PZT.…”
Section: Introductionmentioning
confidence: 99%